Manipulative rhetoric and post-war reconstruction in President Johnson-Sirleaf’s first inaugural address - Adegoju, Adeyemi (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
Following the devastating consequences of Liberia’s fourteen-year civil war for the people and the country at large, the task of mobilising the people and reinforcing their commitment to the cause of nation (re)building rests not only on the leader’s vision but also on how they expressly share the vision with their followers. This paper examines how President Ellen Johnson Sirleaf tailors certain rhetorical strategies in her first inaugural speech of 16th January 2006 to tuning up the Liberian people’s mindset to embrace her vision and imbibe the attitude necessary for the attainment of social and political goals in post-war Liberia. Applying the principles of the socio-cognitive model of Critical Discourse Analysis (CDA) as espoused by van Dijk (2006) to the analysis of the text of the inaugural address, the study interrogates the manipulative nature of the discourse even when it appears that the speaker is mobilising the people for a common goal. The study observes that the asymmetrical relations between the political public speaker and the audience offer the former the latitude to exercise some kind of control on the latter on issues of social representations such as knowledge and ideologies in political processes.